Influence of Job Training and Work-Life Balance on Employee Performance with Job Satisfaction as an Intervening Variable: Case Study at the Civil Service and Human Resource Development Agency of Tangerang Regency - Alfarizy, Muhamad Akbar; Prahiawan, Wawan; Imron, Ali; Bin Harun, Asro (PT. Riset Press International, 2025)
The aim of this research is to examine the impact of job training on employees’ performance as well as the significance of work-life balance in improving performance. In addition, it examines the association between job training plus in job satisfaction, along with how work-life balance influences satisfaction levels. The study research aims to evaluate the effect of staff contentment on work outcomes and its mediating role in integrating skills development and work-life balance with employee performance. The study employed a quantitative, descriptive methodology. This approach allows for a systematic measurement of variables and identification of patterns within the employee population. Data collection methods included observation, interviews, reviewing literature, and distributing questionnaires. The study population consisted of all employees at the BKPSDM Office in Tangerang Regency, based on data collected from 71 individuals selected using saturated sampling. Instrument validation and assessments of reliability were carried out on 30 employees outside the sample using IBM SPSS Statistics with Spearman rank correlation. Structural Equation Modelling (SEM) in SmartPLS 4.0 was utilized for data analysis. The analysis reveals that both job training and work-life balance contribute positively and meaningfully to employee performance. They additionally have a beneficial effect on job satisfaction, which subsequently enhances performance and mediates the influence of training Along with professional-personal equilibrium affecting employee results.